2017
DOI: 10.1016/j.ygyno.2016.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Does para-aortic irradiation reduce the risk of distant metastasis in advanced cervical cancer? A systematic review and meta-analysis of randomized clinical trials

Abstract: Purpose To evaluate the impact of the extension of the radiotherapy field cranially toward para-aortic lymph nodes (EF-RT) in advanced cervical cancer. Materials and Methods A systematic search of databases (PubMed, CENTRAL, Clinical Trials) was performed and included studies that were published between 1960 and November 2015 without language restrictions. All randomized clinical trials (RCTs) were analyzed further. All patients must have undergone pelvic radiotherapy and the same systemic therapy in both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
(52 reference statements)
0
19
0
2
Order By: Relevance
“…Our findings are consistent with those of Park et al [ 25 ] and Yap et al [ 26 ]. A recent meta-analysis regarding EF-PRT by Sapienza et al [ 29 ] reported that cancer-related death was not significantly altered (odds ratio, 0.68; CI, 0.45–1.01; p = 0.06), and the potential impact of PALN RT on survival warrants a reconsideration of EF-PRT. Collectively, these results of the present and previous studies indicate that the clinical benefit of EF-PRT with concurrent chemotherapy was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Park et al [ 25 ] and Yap et al [ 26 ]. A recent meta-analysis regarding EF-PRT by Sapienza et al [ 29 ] reported that cancer-related death was not significantly altered (odds ratio, 0.68; CI, 0.45–1.01; p = 0.06), and the potential impact of PALN RT on survival warrants a reconsideration of EF-PRT. Collectively, these results of the present and previous studies indicate that the clinical benefit of EF-PRT with concurrent chemotherapy was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Para-aortic nodes seen on PET/CT images were therefore not targeted with EBRT. While extended fields to include para-aortic nodes significantly decreases the risk of distant metastases and of para-aortic failure, the effects on overall survival are not yet confirmed[57] and extended fields are not standard in a resource-constrained setting such as ours.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, CT images are easily available for measuring body composition change during treatment, and hence, can be used as potential imaging biomarkers to predict outcomes in clinical practice (6,26). Previous studies on the prognosis of LACC (27)(28)(29)(30)(31)(32) have mainly focused on tumor-specific or treatmentrelated factors, such as International Federation of Gynecology and Obstetrics (FIGO) stage, nodal status, pathology, chemotherapy, and radiation field. However, the effect of body composition change during treatment remains unclear in patients with LACC.…”
Section: Introductionmentioning
confidence: 99%